Studies in law, politics and society. Vol. 31 - Sarat, Austin; Ewick, Patricia (Amsterdam ; London : JAI, 2003)
This volume presents articles by an interdisciplinary and international group of scholars spanning the social sciences, humanities, and law. It examines new perspectives on political relationships, politics and legal reform, and law and the family.
On the global stage : law's adaptations and responses. Chaos as uptopia : international criminal prosecution as a challenge to state power / Lisa Hajjar -- Between past and future : the equivocations of the new cosmopolitanism / Robert Fine and Daniel Chernilo -- Negotiating for justice, fighting for law : the dialectic of promoting and settling disputes in the current global era / Michal Alberstein. Exploring new resources for addressing problems in legal theory. Gotta read Kafka : nine reasons why Kafka is critical for the study of law / Klaus Mladek -- The new revenge and the old retribution : insights from Monte Cristo -- Concepts and localities : Badiou, Deleuze and law / Nathan Moore.
Description based on print version record.
Keywords: Sociological jurisprudence; Political sociology; Law & society; Law -- General